An Open-Ended Based Realıstıc Mathematıcs Learnıng Approach To Students' Creatıve Mathematıcal Thınkıng Abılıtıes - Khairizka, Wirda Indri; Wandini, Rora Rizky (Elementary Teacher Education Program, Majalengka University, 2024)
The main focus of this research is the level of students' creative mathematical thinking abilities. This concern arises from students' struggles to master each indicator of creative thinking abilities. The study aims to assess the level of students' creative thinking abilities for each indicator within their creative mathematical thinking using the open-ended iPMRI approach, specifically targeting fifth-grade elementary students. This quantitative study employs a quasi-experimental design. The research population consists of 44 fifth-grade students from SD Negeri 105346 Aras Kabu. The sample was selected through random sampling to identify both the experimental and control groups. Data collection methods included questionnaires, tests administered to each student, and accompanying documentation. The research findings, based on the results of the sig value. (2-tailed) value of 0.000 < 0.05 and a t-count of 12.493 compared to the t-table value of 1.68595 at df 38, indicate that the t-count is significantly greater than the t-table value (t-count > t-table). This result leads to the rejection of H0 and acceptance of H1. Therefore, it can be concluded that the implementation of an open-ended based realistic mathematics learning approach significantly influences the creative mathematical thinking abilities of fifth-grade students at SD 105346 Aras Kabu, Beringin District, during the 2023/2024 academic year